# proof of Chinese remainder theorem

First we prove that $\mathfrak{{a}}_{i}+\prod_{j\neq i}\mathfrak{{a}}_{j}=R$ for each $i$. Without loss of generality, assume that $i=1$. Then

 $R=(\mathfrak{{a}}_{1}+\mathfrak{{a}}_{2})(\mathfrak{{a}}_{1}+\mathfrak{{a}}_{3% })\cdots(\mathfrak{{a}}_{1}+\mathfrak{{a}}_{n}),$

since each factor $\mathfrak{{a}}_{1}+\mathfrak{{a}}_{j}$ is $R$. Expanding the product  , each term will contain $\mathfrak{{a}}_{1}$ as a factor, except the term $\mathfrak{{a}}_{2}\mathfrak{{a}}_{2}\cdots\mathfrak{{a}}_{n}$. So we have

 $(\mathfrak{{a}}_{1}+\mathfrak{{a}}_{2})(\mathfrak{{a}}_{1}+\mathfrak{{a}}_{3})% \cdots(\mathfrak{{a}}_{1}+\mathfrak{{a}}_{n})\subseteq\mathfrak{{a}}_{1}+% \mathfrak{{a}}_{2}\mathfrak{{a}}_{2}\cdots\mathfrak{{a}}_{n},$

and hence the expression on the right hand side must equal $R$.

Now we can prove that $\prod\mathfrak{{a}}_{i}=\bigcap\mathfrak{{a}}_{i}$, by induction  . The statement is trivial for $n=1$. For $n=2$, note that

 $\mathfrak{{a}}_{1}\cap\mathfrak{{a}}_{2}=(\mathfrak{{a}}_{1}\cap\mathfrak{{a}}% _{2})R=(\mathfrak{{a}}_{1}\cap\mathfrak{{a}}_{2})(\mathfrak{{a}}_{1}+\mathfrak% {{a}}_{2})\subseteq\mathfrak{{a}}_{2}\mathfrak{{a}}_{1}+\mathfrak{{a}}_{1}% \mathfrak{{a}}_{2}=\mathfrak{{a}}_{1}\mathfrak{{a}}_{2},$

and the reverse inclusion is obvious, since each $\mathfrak{{a}}_{i}$ is an ideal. Assume that the statement is proved for $n-1$, and condsider it for $n$. Then

 $\bigcap_{1}^{n}\mathfrak{{a}}_{i}=\mathfrak{{a}}_{1}\cap\bigcap_{2}^{n}% \mathfrak{{a}}_{i}=\mathfrak{{a}}_{1}\cap\prod_{2}^{n}\mathfrak{{a}}_{i},$

using the induction hypothesis in the last step. But using the fact proved above and the $n=2$ case, we see that

 $\mathfrak{{a}}_{1}\cap\prod_{2}^{n}\mathfrak{{a}}_{i}=\mathfrak{{a}}_{1}\cdot% \prod_{2}^{n}\mathfrak{{a}}_{i}=\prod_{1}^{n}\mathfrak{{a}}_{i}.$

Finally, we are ready to prove the . Consider the ring homomorphism  $R\to\prod R/\mathfrak{{a}}_{i}$ defined by projection on each component of the product: $x\mapsto(\mathfrak{{a}}_{1}+x,\mathfrak{{a}}_{2}+x,\dots,\mathfrak{{a}}_{n}+x)$. It is easy to see that the kernel of this map is $\bigcap\mathfrak{{a}}_{i}$, which is also $\prod\mathfrak{{a}}_{i}$ by the earlier part of the proof. So it only remains to show that the map is surjective  .

Accordingly, take an arbitrary element $(\mathfrak{{a}}_{1}+x_{1},\mathfrak{{a}}_{2}+x_{2},\dots,\mathfrak{{a}}_{n}+x_% {n})$ of $\prod R/\mathfrak{{a}}_{i}$. Using the first part of the proof, for each $i$, we can find elements $y_{i}\in\mathfrak{{a}}_{i}$ and $z_{i}\in\prod_{j\neq i}\mathfrak{{a}}_{j}$ such that $y_{i}+z_{i}=1$. Put

 $x=x_{1}z_{1}+x_{2}z_{2}+\dots+x_{n}z_{n}.$

Then for each $i$,

 $\mathfrak{{a}}_{i}+x=\mathfrak{{a}}_{i}+x_{i}z_{i},$

since $x_{j}z_{j}\in\mathfrak{{a}}_{i}$ for all $j\neq i$,

 $=\mathfrak{{a}}_{i}+x_{i}y_{i}+x_{i}z_{i},$

since $x_{i}y_{i}\in\mathfrak{{a}}_{i}$,

 $=\mathfrak{{a}}_{i}+x_{i}(y_{i}+z_{i})=\mathfrak{{a}}_{i}+x_{i}\cdot 1=% \mathfrak{{a}}_{i}+x_{i}.$
 $\frac{R}{\prod\mathfrak{{a}}_{i}}\to\prod\frac{R}{\mathfrak{{a}}_{i}}.$
Title proof of Chinese remainder theorem ProofOfChineseRemainderTheorem 2013-03-22 12:57:20 2013-03-22 12:57:20 mclase (549) mclase (549) 8 mclase (549) Proof msc 11A05 msc 11N99 msc 13A15